Characterization of the Components and Pharmacological Effects of Mountain-Cultivated Ginseng and Garden Ginseng Based on the Integrative Pharmacology Strategy - Li, Sen; Wang, Ping; Yang, Wenzhi; Zhao, Chunhui; Zhang, Luoqi; Zhang, Jingbo; Qin, Yuewen; Xu, Haiyu; Huang, Luqi (Frontiers in Pharmacology, 2021)
Panax ginseng C. A. Mey (PGCAM) is a herbaceous perennial belonging to the Araliaceae family, mainly including Mountain-Cultivated Ginseng (MCG) and Garden Ginseng (GG) on the market. We aimed to establish a rapid, accurate and effective method to distinguish 15-year-old MCG and GG using ultra-performance liquid chromatography-quadrupole time-of-flight-tandem mass spectrometry (UPLC-QTOF-MS/MS), and also explored the pharmacological mechanisms of the main components using the Integrative Pharmacology-based Network Computational Research Platform of Traditional Chinese Medicine (TCMIP V2.0; http://www.tcmip.cn/). Altogether, 23 potential quality markers were characterized to distinguish 15-year-old MCG and GG, including ginsenosides Ra2, Rg1, and Ra1, and malonyl-ginsenoside Ra3, etc. The contents of 19 constituents (mainly protopanaxadiol-type) were higher in MCG compared with that in GG, and four constituents (mainly carbohydrate compounds) were higher in GG. The 105 putative targets corresponding to 23 potential quality markers were mainly involved in 30 pathways, which could be divided into 10 models, such as immune regulation, systems (metabolic, nervous, cardiovascular, reproductive), blood-pressure regulation, as well as antitumor, antiaging, antibacterial and anti-inflammatory effects. Furthermore, the potential quality markers of MCG and GG could inhibit the proliferation of breast cancer by regulating the mRNA expression of PSA, S6K, MDM2, and P53 genes by acting on AR, MTOR, PI3K and other targets. The Integrative Pharmacology Strategy may provide an efficient way to identify chemical constituents and explore the pharmacological actions of TCM formulations.